Effects of photoperiod on phytochemical profiles of four Ocimum basilicum genotypes in a hydroponic climate chamber - Pulvirenti, Luana; Ferreri, Tiziana; Strano, Tonia; Zappalà, Federica; Infantino, Sebastiano; Caruso, Caterina; Morrone, Raffaele; D’Antona, Nicola; Barbera, Antonio Carlo; Carrubba, Alessandra; Napoli, Edoardo (Frontiers in Agronomy, 2025)
IntroductionOcimum basilicum L. (basil) is a widely used aromatic plant with recognized functional properties, largely attributed to its rich profile of bioactive secondary metabolites. As demand for year-round high-quality basil increases, alternative approaches that ensure consistent phytochemical profiles are needed. This study aimed to investigate how different photoperiod regimes (6:4, 16:8, and 18:6 h light:dark) affect the composition of volatile organic compounds (VOCs) released from fresh basil tissues, together with the accumulation of polyphenols, and anthocyanins in four basil genotypes (Italian, Rosie, Greek, and Thai) grown under controlled hydroponic conditions.MethodsBasil plants were cultivated for 26 days in a programmable mini-climate cabinet (Horto4), and their phytochemical composition was analyzed using HS-GC/MS and HPLC-UV techniques.ResultsResults showed that photoperiod significantly affected the accumulation of non-volatile compounds across genotypes. The Italian genotype under the 6:4 photoperiod exhibited the highest concentration of total polyphenols (7.96 mg/g d.w.), including chicoric (3.52 mg/g), rosmarinic (2.79 mg/g), and caffeic acids (0.42 mg/g). Anthocyanin levels in the Rosie genotype also decreased with longer light exposure, with pelargonidin/delphinidin-based pigments dropping from 0.84 mg/g under 6:4 to 0.24 mg/g under 18:6. In terms of VOCs, the Thai genotype showed a consistently high content of estragole (up to 90%) regardless of light exposure, while eucalyptol and β-pinene were predominant in the other genotypes.DiscussionThis work demonstrates that photoperiod modulation can serve as a controlled abiotic stressor to fine-tune the phytochemical composition of basil. It provides a framework for controlled-environment modulation of basil tissue phytochemistry, enabling consistent, “ready-to-eat” tissue quality with stable functional properties, supporting the principles of precision agriculture and farm-to-table innovation.